AKRAB KETERLIBATAN MEDIA MASSA ONLINE (NEW MEDIA) DALAM PEMBERITAAN KONFLIK SOSIAL - Widyaningtyas Virgo Kartika (Jurnal Ilmu Komunikasi AKRAB, 2017)
ABSTRACTMass media involvemet in reporting a social conflict event is an inevatibility. It is due to the fact the conflict is a news value, despite of that other news value elemets are proximity, actuality, factuality, human interest and popularity. Presenting news related to a conflict event by related mass media, it brings logical consequence per se towards the position or alignment of the mass media institution against the ongoing domain of the conflict. This article is the study result of the writer applying literature study method in analyzing the involvement of online mass media in reporting social conflict event. The writer writes that there are several interesting points occured when online mass media reporting a social conflict. First, online mass media tends to prioritize actuality in delivering information to public despite of news accuracy (factuality). Second, actuality in delivering news to public will cause reporting news bias. Third, online mass media tends to perform alignment by becoming story teller of a social confliect and plays its role as conflict intensifier and conflict diminisher.Keywords: Online Mass Media, Social Conflict, Mass Media Alignment, Reporting